Analisis Yuridis Prestasi Karyawan PT Sumber Jaya Dalam Perjanjian Ketenagakerjaan Studi Kasus Nomor.276/Pdt.G/2012/PN.Jkt.Sel. - Nayla Putri Abdullah; Natasya Yadila; Happy Sturaya Quratuainniza; Muh Rozi Asri; Dwi Desi Yayi Tarina (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Default refers to a situation where one party to an agreement fails to fulfill or negligently performs its obligations as stipulated in the contract between the creditor and debtor. This study examines a case of default in an employment contract, as seen in the South Jakarta District Court Decision No. 276/Pdt.G/2012/PN.Jkt.Sel, where an employee unilaterally resigned before the contract’s expiration without fulfilling the agreed-upon obligations. The research aims to analyze the legal resolution of default and the judge’s considerations in ruling on the case. Using a normative juridical method with a case study approach, the study concludes that the court ruled the defendant in default and ordered compensation as specified in the employment agreement. The judge’s decision was based on the principles of freedom of contract, pacta sunt servanda, and good faith.